2020
DOI: 10.15406/ppij.2020.08.00285
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: A vital resource in healthcare and medicine

Abstract: There are many biological resources in nature that are essential in relation to health care. Due to their flexible health benefits documented in various epidemiological studies, there has been increasing interest in research on flavonoids from plant sources. Since flavonoids are directly related to human dietary ingredients and health, structure and function relationships need to be evaluated. Flavonoids bioavailability, metabolism, and biological activity depends on the composition, total number of hydroxyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…In addition, it usually depends on flavonoid classes, but it can also vary among individual compounds within a particular class [ 31 ]. Flavonoid bioavailability depends on many properties, such as their molecular weight, chemical structure, and degree of glycosylation, as well as the type of sugar moieties [ 31 , 32 ]. The solubility of flavonoids in water is generally very low; as a consequence, their absorption by oral administration is difficult, thus leading to low bioavailability and low therapeutic effect [ 33 , 34 , 35 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…In addition, it usually depends on flavonoid classes, but it can also vary among individual compounds within a particular class [ 31 ]. Flavonoid bioavailability depends on many properties, such as their molecular weight, chemical structure, and degree of glycosylation, as well as the type of sugar moieties [ 31 , 32 ]. The solubility of flavonoids in water is generally very low; as a consequence, their absorption by oral administration is difficult, thus leading to low bioavailability and low therapeutic effect [ 33 , 34 , 35 ].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Additionally, the food matrix and processing techniques can also impact the bioavailability of flavonoids [ 165 ], while complex structures of flavonoids and higher molecular weights result in poorer bioavailability [ 166 ]. Flavonoids are typically found as glycosides that are conjugated to sugars compared to their aglycone form.…”
Section: Bioavailability Of Flavonoidsmentioning
confidence: 99%
“…Flavonoids represent a typical secondary metabolite class of phenolic compounds generally found as glycosides in plant tissues. Furthermore, they are active nutraceutical ingredients constituting the largest group of plant phenolics 7,8 . The photosynthetic cells of the plant hosts wide varieties of flavonoid compounds 9 containing two to three aromatic C 6 rings bearing at least one hydroxyl group 10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Ferreyra et al 13 further identified three more sub-classes, which are: Aurone, chalcone and proanthocyanidin. Major differences among the three depend on substitution patterns of the aromatic rings in their different structures 8,14 . According to Middleton 15 , variation among flavonoid classes depend on oxidation and substitution pattern of the C ring and individual compounds in a class base on the substitution pattern of the A and B ring, this make them have diverse biological functions.…”
Section: Introductionmentioning
confidence: 99%